2019
DOI: 10.1590/1981-3821201900010001
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Ideological Preferences in Brazilian Elections, 1994-2018: A Municipal-Level Study

Abstract: This article investigates the electorally expressed ideology of Brazilian voters via ecological analysis at the municipal level between 1994 and 2018. Our purpose is to analyze the main conditioners of aggregated patterns of ideology measured at a high spatial resolution. We test four major explanations for the variation in ideology at the municipal level: the effect of incumbent alignments, social modernization, political pluralism, and social inclusion. We ind that although the Brazilian electorate as a whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…); the second concerns the representative's perception about all the other political parties (Where would you position each political party?). Taking into account that each party has an objective ideological position, Zucco, Power, and coauthors estimate the parties' ideological positions in a number of papers (Gatto and Power ; Power and Rodrigues‐Silveira ; Power and Zucco ; Zucco , ; Zucco, Batista, and Power ; Zucco and Lauderdale ; Zucco and Power ). Based on their work, what can we say about political polarization in Brazil since the 1990s?…”
Section: Polarized Politics Institutions and Policy Outcomes In Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…); the second concerns the representative's perception about all the other political parties (Where would you position each political party?). Taking into account that each party has an objective ideological position, Zucco, Power, and coauthors estimate the parties' ideological positions in a number of papers (Gatto and Power ; Power and Rodrigues‐Silveira ; Power and Zucco ; Zucco , ; Zucco, Batista, and Power ; Zucco and Lauderdale ; Zucco and Power ). Based on their work, what can we say about political polarization in Brazil since the 1990s?…”
Section: Polarized Politics Institutions and Policy Outcomes In Brazilmentioning
confidence: 99%
“…Ideological Distance: PSDB and PT, 1994‐2018 Source : Brazilian Legislative Survey (BLS) (Power and Rodrigues‐Silveira ).…”
Section: Polarized Politics Institutions and Policy Outcomes In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported in [Power and Rodrigues-Silveira 2019] presents an ecological analysis of Brazilian elections at the municipal level from 1995 to 2018. They look for ideological alignments over space and time and try to identify four possible explanations regarding the outcomes of the elections, which were: the effect of incumbent alignments, social modernization, political pluralism, and social inclusion.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, the Brazilian party distribution in the last two elections had a sharp veer to the right on the 2016 municipal elections and the 2018 national elections. On those occasions, PT, the more massive left party in Brazil, lost more than half of its presence in municipalities (Power and Rodrigues-Silveira (2019)).…”
Section: Brazilian Political Systemmentioning
confidence: 99%